2015
DOI: 10.3748/wjg.v21.i37.10493
|View full text |Cite
|
Sign up to set email alerts
|

Targeting mast cells in gastric cancer with special reference to bone metastases

Abstract: Bone metastases from gastric cancer (GC) are considered a relatively uncommon finding; however, they are related to poorer prognosis. Both primary GC and its metastatic progression rely on angiogenesis. Several lines of evidence from GC patients strongly support the involvement of mast cells (MCs) positive to tryptase (MCPT) in primary gastric tumor angiogenesis. Recently, we analyzed infiltrating MCs and neovascularization in bone tissue metastases from primary GC patients, and observed a significant correlat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 90 publications
0
11
0
Order By: Relevance
“…They described the presence of mast cells near blood vessels in bone metastases from gastric cancer and found a correlation between mast cell density and microvascular density. The latter observation led to suggest that tryptase inhibitors or KIT tyrosine kinase inhibitors could represent a novel strategy to inhibit tumour-induced angiogenesis and osteoclastic bone resorption [210].…”
Section: Mast Cells In the Immune Contexture Of Human Gastric Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…They described the presence of mast cells near blood vessels in bone metastases from gastric cancer and found a correlation between mast cell density and microvascular density. The latter observation led to suggest that tryptase inhibitors or KIT tyrosine kinase inhibitors could represent a novel strategy to inhibit tumour-induced angiogenesis and osteoclastic bone resorption [210].…”
Section: Mast Cells In the Immune Contexture Of Human Gastric Cancermentioning
confidence: 99%
“…Mast cell density in tumour microenvironment was associated with poor prognosis [129,168,170,198,199,218], tumour angiogenesis [169,198,199,204,219] and the formation of lymph node [168,219] and bone metastases [209]. These observations led to suggest that angiogenesis blockade could represent a promising target for the treatment of gastric cancer [207,210,231,232]. The results of several clinical trials indicate that anti-angiogenic agents improve overall survival, progression-free survival and disease control rate in gastric cancer [233].…”
Section: Outstanding Questions and Conclusionmentioning
confidence: 99%
“…[ 38 ] As is well known, activities of cell surface serine proteases may promote tumor progression. [ 77 ] In this view, the antineoplastic effects of gabexate have been evaluated in treatments of several advanced tumor types including metastatic colorectal cancer, [ 78 ] gastric cancer with bone metastases [ 79 ] and pancreatic cancer. [ 80 ] Interestingly, an in vitro study indicated that only the invasiveness and metastatic processes were impacted by treatment with gabexate, but the proliferation of the tumor cell line was free from the effect.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that bone tumor enhances the PAR-2 expression in sensory nerves [ 116 ]. In addition, recent studies have revealed that tumor-infiltrating mast cells in bone metastatic tumors of gastric cancer promote bone metastatic growth, osteolytic lesions, and CIBP by stimulating angiogenesis [ 117 , 118 ].…”
Section: The Roles Of the Bone Marrow Microenvironment In The Devementioning
confidence: 99%